2022
DOI: 10.36874/riesw.2022.4.7
|View full text |Cite
|
Sign up to set email alerts
|

Historia – płaszczyzna wpływu w relacjach rosyjsko-ukraińskich w latach 2014-2022

Abstract: The analysis of the Russian-Ukrainian relations case study shows two different models of determining contemporary historical memory. The first (Russian) consists of continuing the imperial traditions in historiography and politics of memory, focused on maintaining the superpower myths of the tsarist and Soviet empires. The second (Ukrainian) points to an attempt by researchers and the political class to escape from the influence of Russian historiography as well as to shape their own national historical narrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…The timeframe of the analysis is the period between Russia's annexation of Crimea in 2014 and its open aggression against Ukraine in 2022, during which the new model of political rule was formed in Russia, based on historical policy (Baluk & Doroshko, 2022). Three research question were formulated for the purpose of the study: What main discourses can be identified in Russia's historical policy?…”
Section: Introductionmentioning
confidence: 99%
“…The timeframe of the analysis is the period between Russia's annexation of Crimea in 2014 and its open aggression against Ukraine in 2022, during which the new model of political rule was formed in Russia, based on historical policy (Baluk & Doroshko, 2022). Three research question were formulated for the purpose of the study: What main discourses can be identified in Russia's historical policy?…”
Section: Introductionmentioning
confidence: 99%